2020
DOI: 10.3389/fneur.2020.00795
|View full text |Cite
|
Sign up to set email alerts
|

Brain Plasticity in Charcot-Marie-Tooth Type 1A Patients? A Combined Structural and Diffusion MRI Study

Abstract: Central nervous system involvement has been described in peripheral neuropathies, including different forms of Charcot-Marie-Tooth (CMT) disease. The aim of our study was to systematically investigate possible brain structural modifications in CMT1A patients, using volumetric MRI, and diffusion tensor imaging (DTI). In this prospective crosssectional study, from May 2017 to May 2019, we acquired 3T MRI brain scans of genetically confirmed CMT1A patients and age-and sex-comparable healthy controls. Patients als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…B6 .Morc2a S87L/+ mice showed cerebral cortex damage and cognitive disorder. In addition, cognitive impairment was identified in human CMT patients of various subtypes ( Kasselimis et al, 2020 ; Pontillo et al, 2020 ; Werheid et al, 2016 ). Moreover, CMT2Z patients can develop cognitive impairment ( Ando et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…B6 .Morc2a S87L/+ mice showed cerebral cortex damage and cognitive disorder. In addition, cognitive impairment was identified in human CMT patients of various subtypes ( Kasselimis et al, 2020 ; Pontillo et al, 2020 ; Werheid et al, 2016 ). Moreover, CMT2Z patients can develop cognitive impairment ( Ando et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second‐level RS‐fMRI analysis was performed using the biological parameter mapping toolbox (v3.1, https://www.nitrc.org/projects/rbpm) [19]: first‐level correlation maps of the two groups were statistically analysed to test for possible differences in the FC with the explored seeds, including age, sex and mean motion as confounding covariates. Grey matter (GM) density, provided by each patient's spatially normalized and smoothed GM map, was also included in the analysis as a voxelwise nuisance regressor, in order to correct for possible structural abnormalities [19] which have previously been shown in the brain of CMT1A patients [5,6]; to this end, the effective smoothness of FC maps was computed using AFNI’s 3dFHWMx tool (https://afni.nimh.nih.gov), and the amount of smoothing needed to match FC maps’ spatial resolution was applied to normalized GM maps obtained from T1‐weighted volumes in the fMRI data preprocessing pipeline. Differences were considered significant for P < 0.00125 (0.05 Bonferroni corrected, considering that 32 ROIs were tested separately), corrected for the family wise error rate at cluster level.…”
Section: Methodsmentioning
confidence: 99%
“…Although CMT1A is primarily a peripheral nervous system disease, central nervous system (CNS) involvement has been anecdotally reported in patients with PMP22 duplication [4], and previous studies demonstrated slight structural modifications in the CMT1A brain [5,6]. Furthermore, evidence of altered brain functional activation in response to different tasks has been reported in other peripheral neuropathies [7,8], along with modifications of resting-state networks, extending beyond the solely sensorimotor network involvement [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…26 While not a common or prominent manifestation, there are some case reports of patients with CMT1A exhibiting central nervous system involvement, such as demyelinating lesions, decreased white matter volume on imaging, or cognitive disorders. [27][28][29] CMT1B is caused by heterozygous variations in MPZ, which encodes a transmembrane protein involved in the adhesion of myelin layers around nerve axons (FIGURE 10-2). 30 Typically CMT1B is clinically and electrophysiologically similar to CMT1A; however, MPZ variations can also cause an intermediate phenotype or a later-onset axonal CMT (CMT2J).…”
Section: Key Pointsmentioning
confidence: 99%